Cost-Benefit Analysis of Propane-fueled Portable Generator Conversion Kit in Warri, Nigeria - C. I. Eboigbe; G. O. Jemiriayigbe (Journal of Applied Sciences and Environmental Management)
A cost-benefit analysis is the process of comparing the projected or estimated costs and benefits (or opportunities) associated with a project decision to determine whether it makes sense from a business perspective. Hence, the objective of this paper is to assess the cost-benefit analysis (CBA) of propane-fueled portable generator conversion kit in Warri, Nigeria using appropriate standard techniques. Based on the cost-benefit analysis, the conversion kit yields a $1.92 return for every dollar invested, as shown by the CBA. It is evident from the computed payback period of 0.52 years how quickly the initial expenditure is recovered. Over a three-year period, the predicted savings on maintenance costs is $7.78, and an annual fuel cost savings of $42. The results show that propane-powered generators offer substantial benefits over conventional gasoline generators. Propane burns cleaner, leaves fewer carbon deposits, needs less frequent maintenance, and is less expensive to maintain and use as fuel. Transitioning to propane has a net positive environmental impact since it reduces greenhouse gas emissions and other pollutants, helping to achieve long-term sustainability goals. Our results confirm that propane conversion kits are a viable, sustainable, and affordable choice for portable generators in both residential and commercial settings.